Does higher intensity increase the rate of responders to endurance training when total energy expenditure remains constant?: a randomized controlled trial - Reuter, Marcel; Rosenberger, Friederike; Barz, Andreas; Venhorst, Andreas; Blanz, Laura; Hecksteden, Anne; Meyer, Tim (Sports medicine - open, 2023)
Background: Standardized training prescriptions often result in large variation in training response with a substantial number of individuals that show little or no response at all. The present study examined whether the response in markers of cardiorespiratory fitness (CRF) to moderate intensity endurance training can be elevated by an increase in training intensity. Methods: Thirty-one healthy, untrained participants (46 ± 8 years, BMI 25.4 ± 3.3 kg m−2 and V˙O2max 34 ± 4 mL min−1 kg−1) trained for 10 weeks with moderate intensity (3 day week−1 for 50 min per session at 55% HRreserve). Hereafter, the allocation into two groups was performed by stratified randomization for age, gender and VO2max response. CON (continuous moderate intensity) trained for another 16 weeks at moderate intensity, INC (increased intensity) trained energy-equivalent for 8 weeks at 70% HRreserve and then performed high-intensity interval training (4 × 4) for another 8 weeks. Responders were identified as participants with VO2max increase above the technical measurement error. Results: There was a significant difference in V˙O2max response between INC (3.4 ± 2.7 mL kg−1 min−1) and CON (0.4 ± 2.9 mL kg−1 min−1) after 26 weeks of training (P = 0.020). After 10 weeks of moderate training, in total 16 of 31 participants were classified as VO2max responders (52%). After another 16 weeks continuous moderate intensity training, no further increase of responders was observed in CON. In contrast, the energy equivalent training with increasing training intensity in INC significantly (P = 0.031) increased the number of responders to 13 of 15 (87%). The energy equivalent higher training intensities increased the rate of responders more effectively than continued moderate training intensities (P = 0.012). Conclusion: High-intensity interval training increases the rate of response in VO2max to endurance training even when the total energy expenditure is held constant. Maintaining moderate endurance training intensities might not be the best choice to optimize training gains. Trial Registration German Clinical Trials Register, DRKS00031445, Registered 08 March 2023 - Retrospectively registered, https://www.drks.de/DRKS00031445
Veröffentlicht: 20. Mai 2023
Gesehen am 10.08.2023